Men, masculinities, travel and tourism / Thomas Thurnell-Read ; Mark E Casey - Thurnell-Read, Thomas
This volume brings together established and emerging writers concerned with men's global mobilities and their experiences of and within travel and tourism. Although there is existing work that has focused on gender and tourism, the emphasis on men, masculinities and tourism has been rather limited. While the implicit masculine position of the tourist gaze has been questioned, understandings of specific male tourists have often failed to engage with the gendered notions of independence, adventure, embodiment and 'risk' that underpin much tourism experience and practice. The authors gathered here draw upon a pool of experience and research. In particular, the collection reflects the multiple ways that men 'do' masculinity as they travel and interact with other men or women. The volume offers insights into men's tourism from as far afield as Mexico, the US, China, Taiwan, western and eastern Europe, and more localized identities in the UK.